Negociação e liderança: papel da chefia direta na gestão da pressão - Aylmer, Roberto (2010)
This study aim identifying, through the lens of Human Resources Managers, the correlation between managers' negotiation competencies and the relationship built with their teams. It also aims to probe the existence of a modulating effect between this relationship and the respective team' s pressure perception. One of the challenges that managers face is how to keep a team motivated and mobilized in an increasing pressure environrnent. In the first and second chapter we introduce the theme and define the Problem to be studied. In the third chapter, we walked through labor, organization and human history willing to ground in a timeline the joumey in the search ofbalance laborlaborer, the mankind's place in shaping this history and some important thinkers of people management. This chapter is a door opener for the next one where we study stress, particularly, occupational stress. In this fourth chapter we point the difference between pressure - present in the environrnent - and stress, derived from the individual interpretation. Our interest in this subject comes from the observation that pressure arises when the market suffers a retraction but also arises when it is heated, so, it increases every time. So, if there is a correlation between how teams or a person 'perceives' his leader and the 'pressure around', this information could be useful for people management, particularly addressing occupational stress. We deepen the concept of Social Support, the net that protects the employee in high-pressure contexts with an emphasis on the leader's role as the main source ofthis support. In chapter 5 we deepen in conjlict due to its' impact on occupational stress leveIs. The workplace relationship is, by its nature, a long term relationship and that makes conflict management a relevant issue on manager's agenda. However, the appropriate conflict management depends on the diagnosis (technical approach) and the confidence leveI build in the relationship (relationallevel). Although we are aware that significant part of the conflicts are related to the corporate structure and strategy, we purposely drove our attention to managers and middle leaders that are part of more representative part of the company' s leadership group aiming to provoke ideas that could contribute to the relationships and results improvement. In chapter six we present the Methodology used and in the seventh chapter we discuss the field research results carried with big companies' Human Resource managers. In this chapter we seek, through HR's sight, a perception over the impact of the leadership comparing them using a subjective perception of higher or lower negotiation capabilities with their teams. The research used a flexible grid supported by a semi-structured questionnaire. Data were decoded by Content Analysis method. Due to the sample size, a statistic treatment was not necessary. The evaluation allow infer that there is a straight relationship between a leader behavior over his team stress perception at the workplace. The study pointed the need for a deeper analysis of the issue considering that the literature and the initial results show an important role of immediate report over the team stress leveI perception. Concluding this study, the research offers questions regarding the company and the leader role on dealing with teams under constant pressure.